Targeted treatment of recurrent platinum-resistant ovarian cancer: current and emerging therapies - Gina M Mantia-Smaldone; Robert P Edwards; Anda M Vlad (Cancer Management and Research, 2010)
Gina M Mantia-Smaldone1, Robert P Edwards2, Anda M Vlad31Division of Gynecologic Oncology, Hospital of the University of Pennsylvania, Philadelphia, PA, USA; 2Division of Gynecologic Oncology, Magee-Womens Hospital of the University of Pittsburgh Medical Center, Pittsburgh, PA, USA; 3Department of Obstetrics, Gynecology and Reproductive Sciences, University of Pittsburgh School of Medicine and Magee-Womens Research Institute, Pittsburgh PA, USAAbstract: With advances in surgical techniques and chemotherapeutic agents, mortality rates from epithelial ovarian cancer (EOC) have slightly decreased over the last 30 years. However, EOC still ranks as the most deadly gynecologic cancer with an overall 5-year survival rate of 45%. Prognosis is especially disappointing for women with platinum-resistant disease, where 80% of patients will fail to respond to available therapies. Emerging treatment strategies have subsequently focused on targets which are integral to tumor growth and metastasis. In this review, we will focus on those innovative agents currently under investigation in clinical trials.Keywords: platinum-resistant, ovarian cancer, targeted therapy, immunotherapy, angiogenesis, growth factors